Array analysis of the seismic wavefield of long-period events and volcanic tremor at Arenal volcano, Costa Rica - Almendros González, Francisco Javier (2014)
We use wavefield decomposition methods (time domain cross correlation and frequency domain multiple-signal classification) to analyze seismic data recorded by a dense, small-aperture array located 2 km West of Arenal volcano, Costa Rica, and operated during 2.5 days. The recorded wavefield is dominated by harmonic tremor and includes also spasmodic tremor and long-period (LP) events. We find that the initial stages of LP events are characterized by three different wave arrivals. These arrivals propagate with similar back azimuths pointing to the volcano summit (∼80°N) and increasing apparent slowness of 0.4, 1.1, and 1.7 s/km. Spasmodic tremors cannot be regarded as coherent signals. On the contrary, harmonic tremors are highly coherent, characterized by the stability of the apparent slowness vector estimates. Apparent slowness lays in the range 1–2 s/km. Back azimuths point in the general direction of the volcano but with a large variability (40–120°N). Nevertheless, there are long-term variations and evidences of multiple simultaneous components in the harmonic tremor wavefield. These observations suggest that LP events and tremor are generated in a shallow source area near the volcano summit, although they do not share exactly the same source region or source processes. The tremor source is located in the shallowest part of the plumbing system, beneath the lava crust. This dynamic region is subject to complex fluctuations of the physical conditions. Degassing events at different locations of this region might generate variable seismic radiation patterns. The effects of topography and heterogeneous shallow structure of the volcano may amplify these variations and produce the wide directional span observed for volcanic tremor. On the other hand, the LP source seems to be more repeatable. LP events are likely triggered by fragmentation of the fluid flow in a slightly deeper portion of the volcanic conduits.